REPRESENTASI MASKULINITAS DALAM IKLAN “BOYS DON’T CRY” WHITE RIBBON - Ajeng Nur Fauziah; Stara Asrita (Kinesik, 2023)
This rigid construction of gender roles causes a bad influence on a man which can then turn into toxic masculinity. Many organizations in the world have carried out a movement to defend the issue of gender equality, one of which is the movement carried out by the White Ribbon in defending healthy masculinity. This study uses a qualitative method with a descriptive approach. The analytical technique used is Fairclough's critical discourse analysis, collecting data by observation by observing the video campaign "Boys Don't Cry" on the White Ribbon youtube channel then researchers also collect data through documentation by taking screenshots of the scene to be studied, then analyze it using critical discourse analysis and present it into the discussion. The results of the study show that this video campaign provides an overview of people who still practice traditional masculinity or toxic masculinity and the negative impacts that accompany it. Like other video campaign functions, the purpose of making this "Boys Don't Cry" video is to persuade the public to defend the rights of men more appropriately and for a healthier masculinity.